Pengaruh ASI Smart Game terhadap Pengetahuan dan Breastfeeding Self Efficacy (BSE) pada Ibu Primipara - Lissa Ervina; Linda Linda; Reka Lagora Marsofely; Ade Febryanti (Media Ilmiah Kesehatan Indonesia, 2026)
Exclusive breastfeeding (EBF) is a crucial strategy for improving infant health and preventing stunting. However, the coverage of exclusive breastfeeding remains low across various regions in Indonesia. The success of EBF is influenced by several factors, particularly maternal knowledge and Breastfeeding Self-Efficacy (BSE). Primiparous mothers are more vulnerable to breastfeeding challenges due to limited experience and low self-confidence. ASI Smart Game is a game-based health promotion tool designed to improve knowledge and BSE among primiparous mothers. This study aimed to evaluate the effect of ASI Smart Game on knowledge and BSE in primiparous mothers. A pre-experimental design using a one-group pretest–posttest approach was employed. The sample consisted of 33 primiparous mothers with infants aged 0–6 months in the working area of Kandang Public Health Center, selected through purposive sampling. Research instruments included an EBF knowledge questionnaire and the Breastfeeding Self-Efficacy Scale–Short Form (BSES-SF). Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05. The results indicated an increase in knowledge and BSE scores after the ASI Smart Game intervention (p = 0.001). ASI Smart Game was effective in enhancing both knowledge and BSE among primiparous mothers.